Modeling framework for evaluating the impacts of hydrodynamic pressure on hydrologic exchange fluxes and residence time for a large-scale river section over a long-term period. (February 2022) - Bao, Jie; Chen, Yunxiang; Fang, Yilin; Song, Xuehang; Perkins, William; Duan, Zhuoran; Shuai, Pin; Ren, Huiying; Hou, Zhangshuan; Richmond, Marshall; He, Xiaoliang; Scheibe, Timothy
Abstract: Quantifying hydrologic exchange fluxes (HEF) at the river and subsurface interface and their residence times (RT) in subsurface are important for managing the water quality and ecosystem health in dynamic river corridor systems. In this study, a modeling framework is developed for coupling the three-dimensional (3D) multi-phase surface, subsurface flow transport, and numerical tracer model for RT in a large-scale river section over a long period. The framework is utilized to evaluate the impacts of hydrodynamic pressure on HEFs and RT for a 30 km section of the Columbia River in Washington State over a three-year period. Based on comparisons between model simulations with and without considering hydrodynamic pressure, we found that hydrodynamic pressure increases the net HEFs by 7% with river gaining water from the subsurface domain, and leads to slight reduction of RT. Highlights: A modeling framework couples multi-phase surface, subsurface flow transport, and numerical tracer model for residence time. The framework has been utilized to evaluate the hydrologic exchange fluxes and residence time for the Columbia River. Hydrodynamic pressure increases the net hydrologic exchange fluxes by 7% with river gaining water from the subsurface domain.